Other Comprehensive Income (OCI) Influenced by the Covid-19 Pandemic – Illustrated with the Example of Entities Listed on the Warsaw Stock Exchange (GPW) - Prewysz-Kwinto, Piotr (Inne całkowite dochody a pandemia Covid-19 – na przykładzie podmiotów notowanych na Giełdzie Papierów Wartościowych w Warszawie, 2022)
The Covid-19 pandemic is undoubtedly the event that has had the strongest impact on the economic activity of companies in the last two years and was reflected in their financial statements. The aim of the study was to verify whether the effects of the Covid-19 pandemic are visible in the area of other comprehensive income presented in the statement of comprehensive income. The study fits into a wider trend of research concerning financial information presented in this element of a financial statement, but in connection with the current subject of the Covid-19 pandemic. The study presents the results of the research on the OCI value in the statements of comprehensive income of the 91 largest entities listed on the Warsaw Stock Exchange. The comparative analysis covered data from the pandemic period (2020-2021) and the year before it (2019).
Financial Sciences. Nauki o Finansach, 2022, vol. 27, no. 1, s. 28-43
Keywords: other comprehensive income; financial statement; IFRS; pandemic; COVID-19; inne całkowite dochody; sprawozdanie finansowe; MSSF; pandemia